ASSOCIATION OF CYSTITIS WITH PREGNANCY COMPLICATIONS: FROM ASYMPTOMATIC BACTERIURIA TO PREECLAMPSIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Risk factors for acute cystitis include a history of ASB, anatomical abnormalities of the urinary tract, gestational diabetes mellitus, and a previous episode of pyelonephritis. Pregnant women experience a higher frequency of recurrences, often associated with the growth of multidrug-resistant strains of E. coli and impaired antibiotic susceptibility . Both asymptomatic bacteriuria and acute cystitis are considered conditions associated with an increased risk of adverse gestational outcomes. The most significant consequence of ASB is its progression to an ascending infection, whereas acute cystitis can contribute to the activation of systemic inflammation and impaired placental perfusion, especially in the absence of timely treatment.